Anukta Vyadhi Nidana through the Principles of Charaka's Nidana Sthana - Konica Gera; Nellufar Siddique; Baldev Kumar (Wolters Kluwer Medknow Publications, 2024)
OBJECTIVE: Goal 3 (SDG) of the 2030 Agenda for Sustainable Development, adopted by India in 2015, seeks to "Ensure healthy lives and promote well-being for all at all ages" by 2030 and covers 13 broad target areas. Diagnosis is a major milestone in disease identification and, hence, planning of management. Charaka Samhita, which is the major treatise of Ayurveda explains the disease diagnostic principles through eight chapters of Nidana Sthana. Another irony is the Ayurveda texts, documented thousands of years ago, offers cures to the diseases of all the times, many of which were not even prevalent at the time of the documentation of the Samhita and hence are not mentioned in the same. The present paper aims to highlight the competence of the Nidana Sthana of Charaka Samhita in diagnosing diseases that are not listed directly in the same. Data Source: Charaka Samhita, along with its available commentaries and related research works. Review Methods: The Charaka Samhita and its available commentaries were thoroughly explored and critically analyzed to understand the rationale behind the Ashta-Adhyaya of Nidana Sthana and their relevance in decoding the pathogenesis of the unstated diseases through the stated. Contemporary research works in the context were explored and analyzed to elicit evidence. Results and Conclusion: The documentation of scientific writing should be pertinent and comprehensive. Charaka Samhita is documented scientifically, where the relevant data are quoted at specific instances, assuring no repetition, undue elaboration, or abridgment. The Nidana Sthana comprising the eight chapters lays the foundation for diagnosing diseases of diverse pathogenesis due to the dominance of three doshas, which can be applied to understand the unstated conditions based on Yukti.